1996
DOI: 10.1042/bj3180561
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a high-affinity inositol 1,4,5-trisphosphate/inositol 1,4,5,6-tetrakisphosphate binding domain to the pleckstrin homology module of a new 130 kDa protein: characterization of the determinants of structural specificity

Abstract: We have previously identified a novel 130 kDa protein (p130) which binds Ins(1,4,5)P3 and shares 38% sequence identity with phospholipase C-delta 1 [Kanematsu, Misumi, Watanabe, Ozaki, Koga, Iwanaga, Ikehara and Hirata (1996) Biochem. J. 313, 319-325]. We have now transfected COS-1 cells with genes encoding the entire length of the molecule or one of several truncated mutants, in order to locate the region for binding of Ins(1,4,5)P3. Deletion of N-terminal residues 116-232, the region which corresponds to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 34 publications
1
60
0
Order By: Relevance
“…PRIP-1 is a novel Ins(1,4,5)P 3 binding protein, which has a number of binding partners, including GABARAP and PP1␣ (Takeuchi et al, 1996(Takeuchi et al, , 1997Yoshimura et al, 2001;. Although the precise cellular function of PRIP-1 remains unknown, deletion of this protein in mice produces GABA A receptors with modified pharmacological properties and behavior, suggesting a role for PRIP-1 in facilitating receptor assembly or activity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRIP-1 is a novel Ins(1,4,5)P 3 binding protein, which has a number of binding partners, including GABARAP and PP1␣ (Takeuchi et al, 1996(Takeuchi et al, , 1997Yoshimura et al, 2001;. Although the precise cellular function of PRIP-1 remains unknown, deletion of this protein in mice produces GABA A receptors with modified pharmacological properties and behavior, suggesting a role for PRIP-1 in facilitating receptor assembly or activity .…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipase C (PLC)-related inactive protein type 1 (PRIP-1) is a novel inositol 1,4,5-trisphosphate [Ins(1,4,5)P 3 ] binding protein (Kanematsu et al, 1992;Yoshida et al, 1994), which is homologous to PLC-␦1 but catalytically inactive (Kanematsu et al, 1992Yoshida et al, 1994;Takeuchi et al, 1996Takeuchi et al, , 1997Takeuchi et al, , 2000. PRIP-1 has a number of binding partners, including catalytic subunit of protein phosphatase 1␣ (PP1␣) and GABA A receptor-associated protein (GABARAP) Yoshimura et al, 2001; Kanematsu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Because our data indicate that the effect of Ins(1,4,5,6)P 4 on Cl Ϫ secretion was downstream of PtdIns3K, it is possible that Ins(1,4,5,6)P 4 competes with PtdInsP 3 for effector binding sites because Ins(1,4,5,6)P 4 is a partial structural analog of the PtdInsP 3 headgroup (27). As a result, Ins(1,4,5,6)P 4 could compete with phosphoinositide binding to pleckstrin homology domains of signaling proteins and inhibit the normal recruitment of signal transduction complexes to the plasma membrane (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of a p130-related molecule in such a simple organism as C. elegans suggests that this family of proteins diverged early from other PLC isozymes. We propose that this distinct family of PLC-related proteins be designated the PLC-related catalytically inactive protein (PRIP) family (comprising PRIP-1 and -2 subfamilies).To investigate the physiological functions of PRIP family proteins, we previously examined the possible role of the binding of inositol compounds to the PH domain of p130 (10,(15)(16)(17). Our results suggested that p130, which is localized predominantly in the cytoplasm, contributes to Ins(1,4,5)P 3 -mediated Ca 2ϩ signaling.…”
mentioning
confidence: 99%